Pediatric eye injuries in upper Egypt - El-Sebaity DM (Dove Medical Press, 2011)
Dalia M El-Sebaity1, Wael Soliman1, Asmaa MA Soliman2, Ahmed M Fathalla11Department of Ophthalmology, Assiut University Hospital, Assiut, Egypt; 2Department of Public Health and Community Medicine, Faculty of Medicine, Assiut University, Assiut, EgyptPurpose: To analyze the patterns, causes, and outcome of pediatric ocular trauma at Assiut University Hospital in Upper Egypt (South of Egypt).Methods: All ocular trauma patients aged 16 years or younger admitted to the emergency unit of Ophthalmology Department of Assiut University between July 2009 and July 2010 were included in the study. The demographic data of all patients and characteristics of the injury events were determined. The initial visual acuity and final visual acuity after 3 months follow-up were recorded.Results: One hundred and fifty patients were included. The majority of injuries occurred in children aged 2–7 years (50.7%). There were 106 (70.7%) boys and 44 (29.3%) girls. The highest proportion of injuries occurred in the street (54.7%) followed by the home (32.7%). Open globe injuries accounted for 67.3% of injuries, closed globe for 30.7%, and chemical injuries for 2%. The most common causes were wood, stones, missiles, and glass. LogMar best corrected visual acuity at 3 months follow-up was: 0–1 in 13.3%; <1–1.3 in 27.3%; <1.3–perception of light (PL) in 56%; and no perception of light (NPL) in 3.3%.Conclusions: Pediatric ocular trauma among patients referred to our tertiary ophthalmology referral center in Upper Egypt over a period of 1 year was 3.7%. Of these, 67.3% of cases had open globe injury, 30.7% had closed injury, and only 2% had chemical injury. In Upper Egypt, socioeconomic and sociocultural status, family negligence, and lack of supervision are important factors in pediatric eye injuries, as 92% of children were without adult supervision when the ocular trauma occurred. Nearly 86.6% of children with ocular trauma end up legally blind. Modification of these environmental risk factors is needed to decrease pediatric ocular morbidity.Keywords: ocular trauma, pediatric, epidemiology